2023
DOI: 10.3233/jad-230121
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease-Related Phospho-Tau181 Signals Are Localized to Demyelinated Axons of Parvalbumin-Positive GABAergic Interneurons in an App Knock-In Mouse Model of Amyloid-β Pathology

Abstract: Background: The tau protein phosphorylated at Thr181 (p-tau181) in cerebrospinal fluid and blood is a sensitive biomarker for Alzheimer’s disease (AD). Increased p-tau181 levels correlate well with amyloid-β (Aβ) pathology and precede neurofibrillary tangle formation in the early stage of AD; however, the relationship between p-tau181 and Aβ-mediated pathology is less well understood. We recently reported that p-tau181 represents axonal abnormalities in mice with Aβ pathology (AppNLGF). However, from which neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…While most researchers focused on neuronal tau, Hirota et al. reported that AD‐related p‐tau181 signals localized to demyelinated axons of parvalbumin‐positive GABAergic interneurons in an App knock‐in mouse model of AD 109 . Of note, oligodendroglial tau could propagate along WM tracts, resulting in the loss of OLs.…”
Section: Study Designs and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most researchers focused on neuronal tau, Hirota et al. reported that AD‐related p‐tau181 signals localized to demyelinated axons of parvalbumin‐positive GABAergic interneurons in an App knock‐in mouse model of AD 109 . Of note, oligodendroglial tau could propagate along WM tracts, resulting in the loss of OLs.…”
Section: Study Designs and Methodsmentioning
confidence: 99%
“…reported that AD-related p-tau181 signals localized to demyelinated axons of parvalbumin-positive GABAergic interneurons in an App knock-in mouse model of AD. 109 Of note, oligodendroglial tau could propagate along WM tracts, resulting in the loss of OLs. Moreover, this process was independent of neuronal tau.…”
Section: Ols Also Participate In Other Ad Pathologiesmentioning
confidence: 99%
“…The PNN is one of the master regulators of E/I balance [ 154 ], and reduced PNN expression has been observed in human AD brains and rodent models [ 155 , 156 ], while astrocytes and resident macrophages of the brain called microglia also regulate PV+ cell excitability ( Figure 1 ) [ 157 , 158 ]. In addition, PV+ cell axons are highly myelinated [ 159 ] and one recent report found evidence of demyelination of PV+ axons, but not excitatory neurons, at early disease stages in an AD mouse model [ 160 ]. While the causes of PV cell vulnerability in diseases have often focused on their high energy demands, as discussed in this review, changes in the PNN and/or myelination levels would also have profound effects on PV+ neuron's firing properties and function [ 161 ].…”
Section: Parvalbumin Neuron Deficits In Alzheimer's Disease and Demen...mentioning
confidence: 99%